4‐Formyl‐Pyrazole‐3‐Carboxylate: A Useful Aldo‐X Bifunctional Precursor for the Syntheses of Pyrazole‐fused/Substituted Frameworks. (5th December 2017) - Devi, Nisha; Shankar, Ravi; Singh, Virender
Abstract : Pyrazole, a privileged class of heterocyclic compounds, constitute an interesting template for medicinal chemistry and is represented by several commercial drugs like Sildenafil, Zometapin, Celebrex, and Rimonabant. The presence of two functionalities with different reactivity in pyrazole moiety may open new avenues for insertion of diversity in pyrazole frameworks which may be of high medicinal significance. Ethyl 4‐formyl‐1 H ‐pyrazole‐3‐carboxylate is a potential Aldo‐X bifunctional building block (AXB3) which may be explored for generating complex pyrazole based molecular frameworks by using various organic transformations. The present manuscript is assimilation of literature pertaining to the synthesis and application of ethyl 4‐formyl‐1 H ‐pyrazole‐3‐carboxylates and similar AXB3 for the development of pyrazole substituted and fused derivatives. Abstract :